PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KOMPETENSI GURU, BUDAYA SEKOLAH, DAN DISIPLIN KERJA TERHADAP KINERJA GURU PAI SMP KABUPATEN TEMANGGUNG - Murbaningtyas, Indriyanti; Suwito Eko Pramono; Sugi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of principal leadership, teacher competence, school culture, and work discipline on the performance of Islamic Education (PAI) teachers at Junior High Schools (SMP) in Temanggung Regency. The background of this research is based on the low achievement of teacher performance indicators, specifically in developing teaching modules and elaborating learning outcomes in the field, as well as the low education report card scores in the region.This research employs a quantitative approach with a hypothesis testing study design. The research population consists of all Junior High School PAI teachers in Temanggung Regency registered in the SIAGA account, with a sample size of 87 respondents determined using the Slovin formula. Data were collected through observation, interviews, and questionnaires, and subsequently analyzed using descriptive and inferential statistical techniques assisted by SPSS software.The results indicate that, simultaneously, principal leadership, teacher competence, school culture, and work discipline have a significant influence on teacher performance, with an Adjusted R Square value of 84.6%. Partially, the hypothesis testing shows that: (1) Principal leadership has no significant influence on teacher performance (Sig. 0.913 > 0.05); (2) Teacher competence has a significant influence on teacher performance (Sig. 0.002 < 0.05); (3) School culture has a significant influence on teacher performance (Sig. 0.003 < 0.05); and (4) Work discipline has a significant influence on teacher performance (Sig. 0.025). These findings emphasize that internal teacher factors (competence and discipline) and the work environment (school culture) play a more dominant role in determining the performance of PAI teachers compared to the direct managerial role of the principal in this specific context.